A CaMoO4 crystal low temperature detector for the AMoRE neutrinoless double beta decay search - Kim, G. B.; Choi, S.; Danevich, F. A.; Fleischmann, Andreas; Kang, C. S.; Kim, H. J.; Kim, S. R.; Kim, Y. D.; Kim, Y. H.; Kornoukhov, V. A.; Lee, H. J.; Lee, J. H.; et al. (Advances in high energy physics, 2015)
We report the development of a CaMoO4 crystal low temperature detector for the AMoRE neutrinoless double beta decay search experiment. The prototype detector cell was composed of a 216 g CaMoO4 crystal and a metallic magnetic calorimeter. An overground measurement demonstrated FWHM resolution of 6-11 keV for full absorption gamma peaks. Pulse shape discrimination was clearly demonstrated in the phonon signals, and 7.6  of discrimination power was found for the and separation. The phonon signals showed rise-times of about 1 ms. It is expected that the relatively fast rise-time will increase the rejection efficiency of two-neutrino double beta decay pile-up events which can be one of the major background sources in searches.
Gesehen am 01.07.2020